Biodiversitas Crustaceae Di Kawasan Mangrove Tutuwoto Kecamatan Anggrek Kabupaten Gorontalo Utara - SM, Farid; Gobel, Siti Amalia (Jurnal Biologi Babasal, 2023)
Abstract: An area of 11 hectares is Tutuwoto Village, North Gorontalo Regency, located there (KPH Gorut, 2010). Tutuwoto Village, Anggrek District, North Gorontalo Regency: The Mangrove Area was used as the location of this research. The three month period from April to June 2018 when this research was conducted. Crustacean samples were collected using simple fishing gear in the form of nets, nets and seser. Species abundance was calculated using the formula Odum, (1996). Calculation of diversity using the formula (Sannon-Wienner). The composition of the crustaceans numbered 110 individuals, consisting of 7 species, Scylla serrata 15 individuals, Scylla olivacea 14 individuals, Scylla tranquebarica 13 individuals, Carcinus maenas 14 individuals, Metapenaeus elegans 19 individuals, Penaeus latisulcatus, 20 individuals and Metapenaeus affinis 15 individuals. Based on the ODUM standard, the crustacean diversity values at the study sites ranged from 1.10 to 1.39. In 1993, the crustaceans at the study site were classified as medium because the value of 1H' was 3. With a value of 37.04%, Penaeus latisulcatus had the greatest abundance, and 26.79% of the family Portunidae dominated Scylla serrata. Type Many crustaceans are in the abundance category for all types according to Michael's criteria (1995) because the K value is more than 20. All locations generally have favorable environmental conditions for crustacean and mangrove life